Biochemical Characterization of Liver Oil of Echinorhinus brucus (Bramble Shark) and Its Cytotoxic Evaluation on Neuroblastoma Cell Lines (SHSY-5Y) - Vishnu Venugopal; Ajeeshkumar Kizhakkepurath Kumaran; Niladri Sekhar Chatterjee; Suvanish Kumar; Shyni Kavilakath; Jayarani Ramachandran Nair; Suseela Mathew (Scientifica)
The objective of the present study was to characterize the liver oil extracted from the deep sea shark, Echinorhinus brucus, caught from Central Indian Ocean and to evaluate its cytotoxic effect on neuroblastoma cell line (SHSY-5Y). Characterization of liver oil of Echinorhinus brucus revealed the presence of palmitic acid (15%), oleic acid (12%), stearic acid (8%), docosahexaenoic acid (DHA) (18%), and eicosapentaenoic acid (EPA) (16%). It was also found to be a good source of squalene (38.5%) and fat soluble vitamins such as A, D, and K (vitamin A: 17.08 mg/100 g of oil, vitamin D: 15.04 mg/100 g oil, and vitamin K: 11.45 mg/100 g oil). Since it was found to be rich in essential fatty acids, fat soluble vitamins, and squalene, it can be considered as better dietary supplement. The oil of Echinorhinus brucus also showed high in vitro cytotoxic effect against the human neuroblastoma cell line (SHSY-5Y) and the IC50 value laid between 35 and 45 ng.